The Effects of the Dobbs Decision on Fertility - Daniel Dench; Mayra Pineda-Torres; Caitlin Knowles Myers (Institute of Labor Economics (IZA), 2023)
The U.S. Supreme Court decision in Dobbs v. Jackson Women's Health Organization sparked the most profound transformation of the landscape of abortion access in 50 years. We provide the first estimates of the effects of this decision on fertility using a pre-registered synthetic difference-in-differences design applied to newly released provisional natality data for the first half of 2023. The results indicate that states with abortion bans experienced an average increase in births of 2.3 percent relative to states where abortion was not restricted.
Keywords: I11; I12; I18; J13; K23; 330; abortion; Dobbs; fertility; power analysis